2009
DOI: 10.1108/17410380910953702
|View full text |Cite
|
Sign up to set email alerts
|

Development of a manufacturing flexibility hierarchy through factor and cluster analysis

Abstract: PurposeThe ability of production organizations to respond quickly to changes in the market with new products requires flexibility. The relationship between manufacturing flexibility and the performance of organizations in new product development is not well characterized. The purpose of this paper is to develop and test a flexibility model focused on new product performance in manufacturing organizations empirically in one industrial sector.Design/methodology/approachHypothesized relationships between manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 60 publications
(89 reference statements)
0
36
0
Order By: Relevance
“…Particularly, we found the strong positive relationship between new product flexibility and machine flexibility. According to the study of Larso et al,2009, new product flexibility is positively associated with volume, operation and routing flexibility. These factors are antecedents for improving market flexibility.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Particularly, we found the strong positive relationship between new product flexibility and machine flexibility. According to the study of Larso et al,2009, new product flexibility is positively associated with volume, operation and routing flexibility. These factors are antecedents for improving market flexibility.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The total design method (Larso and Doolen, 2009) was used to develop survey items and the survey administration. Survey items were adapted from previously published studies, wherever available.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, the total design method (Larso, Doolen, & Hacker, ) was used to develop survey items and guide survey administration. Survey items were adapted from previously published studies, wherever available.…”
Section: Methodology Of the Present Studymentioning
confidence: 99%
“…Indian service firms in the banking and IT sectors were selected as the target population for this research. Mutula and Brake (2007) reported that IT innovation and adaptation to changes were the two For this study, the total design method (Larso, Doolen, & Hacker, 2009) was used to develop survey items and guide survey administration. Survey items were adapted from previously published studies, wherever available.…”
Section: Methodology Of the Present Studymentioning
confidence: 99%